Analisis Minat Beli Konsumen Muslim Terhadap Produk Makanan Kemasan Yang Tidak Memiliki Sertifikasi Label Halal - Alfiyah Syifa Idztihar; Arumsari Arumsari; Fatimah Nur Salsabila Rahmatul Ummah; Ateng Supriatna; Tri Cahyanto (Jurnal Akuntan Publik, 2023)
The high interest in packaged food products in Indonesia, as a country with a predominantly Muslim population, requires halal packaged food products in accordance with Islamic law to use its products. Therefore, even though every product has a halal logo for consumer safety, the presence of a halal label on packaged food can influence consumer buying interest in purchasing packaged food products. The purpose of this research is to find out how Muslim consumers buy interest in packaged food products that do not have halal certification. The method used is descriptive analysis method and the results obtained are analyzed qualitatively. Data acquisition resulted from questionnaires distributed randomly to people who are Muslim. The results of the study show that the public's understanding of halal label certification is quite good. Halal label certification is a very important element in a packaged food product. Every food product must include a halal label. The issuance of halal label certification is sufficient to influence people's decisions in buying packaged food products, with the existence of halal label certification it gives a sense of security and confidence to the public in buying packaged food.